Kdo podává žádost o rozvod a jaké jsou příčiny rozpadu partnerských vztahů? - Marta Vohlídalová (Gender a Výzkum, 2010)
The paper focus on two main questions: (i) who is the initiator of divorces and what socio ‑demographic and life‑cycle characteristics determine whether the man or the woman files for a divorce; and (ii) what are the individual reasons and motives that lead to the breakup of marriages and consensual unions and what socio ‑demographic characteristics (e.g. education, number of children, age, etc.) influence people’s perceptions of these reasons? The analysis is based on two data sources: the database of divorces for the year 2008 registered by the Czech Statistical Office and the quantitative survey ‘Partnership’ conducted in 2009, which included a representative sample of 1086 respondents. The author concludes that the fact of who initiates divorce is closely related to the individual’s potential chances or risks of divorce. Regarding the subjective reasons of partnership breakup, the data showed a clear tendency for younger people, childless couples and people in consensual unions to cite reasons closely related to the quality of a relationship and emotional satisfaction arising from the relationship. In contrast, long ‑term partnerships, marriages or partnerships with children break up more often for reasons of infidelity, alcoholism or violence.